The Impact Of Ceo Characteristics And Ownerships On Risk-Taking Behaviour Among Publicly Listed Family Companies In Malaysia - Wasim, Omair (2024)
This study aims to examine the effects of chief executive officer (CEO) characteristics and CEO ownership on the risk-taking behaviour among publicly listed family companies in Malaysia. Risk-taking behaviour can be examined by employing the debt-to-equity (D/E) and debt-to-asset (D/A) ratios as measurement variables. The characteristics of a CEO are assessed based on factors such as the age, level of education, gender, and generational of the CEO. CEO ownership level is measured by CEO ownership. Feasible generalized least squares (FGLS) are adopted for the analysis of debt-to-equity ratio (D/E) and debt-to-asset ratio (D/A). By analysing a sample of 65 Malaysian family companies traded on the Bursa Malaysia during the period of 2014 till 2020, the findings show that CEO undergraduate degree, CEO postgraduate degree and CEO generation is significantly related to risk-taking behaviour using debt-to-equity ratio (D/E). Whereas, CEO gender, CEO undergraduate degree and CEO professional qualification is significantly associated to risk-taking behaviour using debt-to-asset ratio (D/A). This study provides evidence to all the companies hiring CEOs that the educational background of CEOs plays a crucial role in explaining the variances in risk-taking behaviour observed across family-owned businesses. This finding aligns with the principles of the upper echelons theory (UET). It is encouraged for the future research to increase the sample size to obtain a more accurate result. The present study provides practical evidence to the academicians, policymakers specifically in Malaysia and all related parties in emerging economies.